Incidencias de oportunidades económicas y sociales en tecnologías de cuarta revolución industrial en Colombia (2020)
In Colombia like the rest of Latin-American countries, the first industrial revolution arrived really late compared with North America and the western European countries, that is why almost all the countries in the region lagged behind in terms of product innovation, economic growth and a solid welfare state. Currently, Colombia is in a distant position on the many lists that measure how industrialized a country is, as well as the ones that measure how many inventions and patents a country creates. With this environment in mind, in the last twenty years a series of extremely revolutionaries technologies have appeared that promise to change the way our society, our governments and companies fundamentally work. All this can be a wonderful opportunity for economic growth and therefore for the creation of new job offers, that will help to increase formal employment and the reduction of poverty in Colombia. For this reason, this article is conceived from the need to analyze the impact that this fourth industrial revolution may bring to Colombia through the use of an descriptive investigation with a qualitative approach in which several sources of information will be used such as magazine articles, degree thesis, government agencies reports and business adoption reports from Colombian companies that have already started the process of embracing this new technologies with the hope of finding the key answer of how Colombian society can take advantage of this new technologies that this revolution offers.